Response of benthic foraminifera to environmental successions of cold seeps from Vestnesa Ridge, Svalbard: Implications for interpretations of paleo-seepage environments - Melaniuk, Katarzyna; Sztybor, Kamila; Treude, Tina; Sommer, Stefan; Zajączkowski, Marek; Rasmussen, Tine L. (Frontiers in Marine Science, 2022)
This paper presents the results of a study on the response of living benthic foraminifera to progressing environmental successions in a cold-seep ecosystem. Sediment samples were collected from Vestnesa Ridge (79°N, Fram Strait) at 1200 m water depth. The distribution of live (Rose Bengal-stained) foraminifera were analyzed in the upper sediment layers in relation to pore water biogeochemical data together with the distribution of sulfur-bacterial mats and Siboglinidae tubeworms. At methane cold seeps, the process of environmental succession is strongly connected to the duration and strength of methane seepage and the intensity of methane-related biological processes, e.g., aerobic and anaerobic oxidation of methane (MOx and AOM, respectively). The results show that the distribution patterns of benthic foraminifera change according to the progressing environmental succession. The benthic foraminifera seemed to thrive in sediments with a moderate activity of seepage, dominated by MOx, i.e., at an early stage of seepage or when seepage decreases at a late stage of the succession. Species composition of the foraminiferal fauna under these conditions was similar to the control sites (outside of pockmarks with no seepage); the dominant species being Melonis barleeanus and Cassidulina neoteretis. In sediments with strong seepage and high AOM activity, the hostile environmental conditions due to the presence of toxic sulfide caused a reduction in the foraminiferal population, and samples were almost barren of foraminifera. In environments of moderate methane seepage, the presence of chemosynthetic Siboglinidae tube worms potentially support communities of the epibenthic species Cibicidoides wuellerstorfi. Despite the very different environmental conditions, the foraminiferal assemblages were very similar (or nearly absent). Therefore, the foraminiferal faunas cannot be used as exclusive indicators of past strength of methane seepage in palaeoceanographic interpretations.